2017
DOI: 10.1111/jpc.13686
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of neonatal care in the Solomon Islands

Abstract: Infrastructure limitations, technical maintenance and equipment organisation were obstacles to newborn care. Greater health-care worker knowledge and skills for early essential newborn care, infection control and management of newborn complications is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Sources gave numerous examples of lack of sufficient and equitable distribution of HWs-specifically lack of skilled birth attendants and skilled neonatal nurses-with resulting heavy workloads for existing staff and unacceptable staffing ratios. 10,29,33,35,42,44,[47][48][49][50][51][52][53][54][55][56] A study in 2 newborn units in Nairobi public hospitals reported staffing ratios of 1 nurse to 15 babies. 48 Aluvaala et al 10 found that of 22 hospital-based newborn units surveyed in Kenya, 6 had such severe personnel shortages that they were not able to allocate even 1 nurse specifically for each newborn unit.…”
Section: Insufficient and Inequitable Distribution Of Hws And Heavy Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources gave numerous examples of lack of sufficient and equitable distribution of HWs-specifically lack of skilled birth attendants and skilled neonatal nurses-with resulting heavy workloads for existing staff and unacceptable staffing ratios. 10,29,33,35,42,44,[47][48][49][50][51][52][53][54][55][56] A study in 2 newborn units in Nairobi public hospitals reported staffing ratios of 1 nurse to 15 babies. 48 Aluvaala et al 10 found that of 22 hospital-based newborn units surveyed in Kenya, 6 had such severe personnel shortages that they were not able to allocate even 1 nurse specifically for each newborn unit.…”
Section: Insufficient and Inequitable Distribution Of Hws And Heavy Wmentioning
confidence: 99%
“…Poor salaries, inconsistent payment, and substandard accommodations are often reported. 29,31,35,41,42,45,52,53,55,58 A qualitative study carried out with HWs in Cambodia 52 reported low salaries for skilled birth attendants, such that they only provide postnatal care to the mother and newborn if additional payments are made by family members. As noted in HRH challenge 5, HWs often create additional income-generating activities to supplement their incomes.…”
Section: Poor Work Environmentmentioning
confidence: 99%
“…Resident doctors staff provincial hospitals, and most can only deliver vaginal births. Provincial hospital SCN can provide oxygen, antibiotics, and intravenous fluids depending on facility setup and staffing expertise . The Solomon Island Standard Treatment Manual provides basic guidelines on criteria for referral of newborns from smaller facilities to provincial hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…There are complex challenges to improving health care services for mothers and newborns in Solomon Islands. These include challenges in maintenance of health care facilities, distance and transport, environmental conditions (including the effects of climate change, floods, and earthquakes), and health care workforce issues including limited numbers, workforce planning, training, distribution, and few opportunities for skills enhancement . Due to geographical and economic isolation from the only tertiary referral hospital (National Referral Hospital (NRH)) in Honiara, provincial hospitals play a pivotal role in neonatal care.…”
mentioning
confidence: 99%
“…Similar to other lower middle-income countries, in Solomon Islands, most neonatal deaths occur because of complications of preterm birth, intrapartum-related complications, and sepsis. 20,21 Essential newborn care and basic neonatal resuscitation are interventions that have the most impact on reducing preventable neonatal deaths and stillbirths. 22 Essential newborn care practices include clean birth processes, thermal considerations through skin-to-skin contact and ambient temperature control, support and initiation of exclusive breastfeeding, and hygienic cord care, as well as reduction of potentially harmful practices such as early bathing and unnecessary suctioning.…”
Section: Introductionmentioning
confidence: 99%